Structural Build-Up of Cement Pastes: A Comprehensive Overview and Key Research Directions - Mahmoud Hayek; Youssef El Bitouri; Kamal Bouarab; Ammar Yahia (Construction Materials, 2025)
The advancement of modern concretes, such as printable concrete, fluid concrete with adapted rheology, and ultra-high-performance concrete, has increased the importance of understanding structural build-up in cement-based materials. This process, which describes the time-dependent evolution of rheological properties, is a key factor to ensure the stability of concrete by influencing segregation, bleeding, formwork pressure, numerical modeling, and multi-layer casting. As a result, the structural build-up of cementitious materials has become a significant area of research in recent years. The structural build-up of cement based-materials results from both a reversible part (thixotropic behavior), driven by colloidal interactions, and an irreversible part, caused by cement hydration and the formation of C-S-H bridges. Various experimental techniques have been developed to investigate these processes, with various factors affecting the thixotropic behavior and overall structural build-up of cement suspensions. This review provides a comprehensive analysis of the current understanding of structural build-up in cement pastes. It covers measurement methods and key influencing factors, including the water-to-binder ratio (w/b), admixtures, temperature, and supplementary cementitious materials (SCMs). By consolidating the existing knowledge and identifying research gaps, this review aims to contribute to the development of sustainable, high-performance cement-based materials suitable for modern construction techniques.